Heliorhodopsins are absent in diderm (Gram-negative) bacteria: Some thoughts and possible implications for activity - Flores-Uribe, José; Hevroni, Gur; Ghai, Rohit; Pushkarev, Alina; Inoue, Keiichi; Kandori, Hideki; Béjà, Oded (Environmental microbiology reports, 2019)
Microbial heliorhodopsins are a new type of rhodopsins, currently believed to engage in light sensing, with an opposite membrane topology compared to type-1 and type-2 rhodopsins. We determined heliorhodopsins presence/absence is monoderms and diderms representatives from the Tara Oceans and freshwater metagenomes as well as metagenome assembled genome collections. Heliorhodopsins are absent in diderms, confirming our previous observations in cultured Proteobacteria. We do not rule out the possibility that heliorhodopsins serve as light sensors. However, this does not easily explain their absence from diderms. Based on these observations, we speculate on the putative role of heliorhodopsins in light-driven transport of amphiphilic molecules.
Keywords: mořská voda; Open Reading Frames; gramnegativní bakterie; Gram-Negative Bacteria; Metagenome; metagenom; Seawater; oceány a moře; biologické modely; sladká voda; otevřené čtecí rámce; senzorické rhodopsiny; Oceans and Seas; Sensory Rhodopsins; Models, Biological; Fresh Water